Variable effects of exercise intensity on reduced glutathione, thiobarbituric acid reactive substance levels, and glucose concentration - Ilhan, N; Kamanli, A; Ozmerdivenli, R; Ilhan, N (Elsevier Science Inc, 2004)
Background. Physical exercise may be associated with a 10- to 20-fold increase in whole body oxygen uptake. Generation of free oxygen radicals (FORs) is elevated to a level that overwhelms tissue antioxidant defense systems in exercise. One of the most reliable indices of exercise-induced oxidant production is tissue glutathione oxidation. Methods. In this study three different volunteer groups carried out various sports disciplines and worked at least as amateurs for 6-7 years before and after aerobic (Aer)-, anaerobic (Anae)-, or aerobic + anaerobic (Aer-Anae)-dominant exercises. Thiobarbituric acid reactive substances (TBARS) reduced glutathione (GSH) levels, glucose concentration was measured, and we investigated their relationships with different types of exercise. From all groups (n = 60, each group comprising 10 females and 10 males), we collected blood samples at the following five different times: before exercise; immediately after exercise, and 4, 24, and 48 It after completion of exercise. These samples were assayed for whole blood GSH, plasma TBARS levels, and glucose concentration. Results. Significant increase in Aer-Anae was noted in levels of TBARS while decrease was observed in glutathione levels in exercise group as compared with prior levels in all groups. However, no statistical difference was observed in total group levels before and after exercise and in male and female groups compared before and after exercise. When gender differences were taken into account, females generally had higher levels of GSH, whereas TBARS levels were higher in males. When compared either before or after exercise, levels of glucose concentration-especially immediately after exercise period in all groups-were higher. In addition, in Anae groups glucose concentrations were higher at 4 and 24 h in females than in males. Aer exercise caused oxidative stress to a lesser degree, whereas Aer-Anae exercise caused oxidative stress of higher degree that was statistically significant. Conclusions. According to our findings, exercise increased TBARS level significantly in all groups, especially more so in Aer-Anae groups. In addition, GSH was increased more in females than in males, while concentration of glucose did not change remarkably. Additionally, it can be stated that women are more resistant to oxidative stress. (C) 2004 IMSS. Published by Elsevier Inc.
Keywords: exercise types; TBARS; reduced glutathione; glucose